Working Women in Cultural: Exploring the Potential of Family Counseling (Indonesian Journal of Counseling and Development, 2023)
In contemporary society, it has become commonplace for women to engage in professional work, leading to intriguing psychological dynamics, particularly within the family unit. The multifaceted role of a woman as a mother, a wife, and an employee generates diverse demands. This research employs a qualitative phenomenological analysis of 10 working women from the Kerinci district, each with distinct backgrounds. Data was scrutinized using qualitative analysis techniques, encompassing theme analysis, Wordchart analysis, and triangulation, facilitated by the Atlas.it application. The study concludes that a woman’s inclination to work is influenced by the family’s economic conditions, pre-marital educational responsibilities, and the need to fulfill tertiary requirements unmet by the husband’s income alone.